Development of a Summation Formula in Connection with Hypergeometric and Gamma Function (Global Journal of Science Frontier Research, 2013)
The aim of this paper is to derive a summation formula based on half argument in connection with Hypergeometric function and involving recurrence relation and Gauss summation theorem.
Keywords: contiguous relation; gauss second summation theorem; recurrence relation